2021
DOI: 10.1001/jama.2021.2275
|View full text |Cite
|
Sign up to set email alerts
|

Consistency Between State Medical License Applications and Recommendations Regarding Physician Mental Health

Abstract: Physicians have higher rates of depression, burnout, and suicide than the general population. 1 Despite this, physicians infrequently seek mental health care, consistently citing fear of negative ramifications for licensing. 2,3 State medical license applications often ask broad questions about mental health history or its hypothetical effect on competency, even though asking violates the Americans With Disabilities Act. In states with license applications that ask such questions, physicians are more reluctant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
0
24
0
2
Order By: Relevance
“…Professionalism education often focuses on broad general principles, rather than on what to do when these and other ethical principles conflict and need to be weighed against each other. Education on professionalism should thus address this situation of doctors not wanting to treat unvaccinated COVID patients, probing why doctors nonetheless have duties to care for these patients, how and why psychological and moral conflicts can nonetheless ensue, and how best to address these challenges [45].…”
Section: Ways Of Addressing Resultant Moral Distressmentioning
confidence: 99%
See 1 more Smart Citation
“…Professionalism education often focuses on broad general principles, rather than on what to do when these and other ethical principles conflict and need to be weighed against each other. Education on professionalism should thus address this situation of doctors not wanting to treat unvaccinated COVID patients, probing why doctors nonetheless have duties to care for these patients, how and why psychological and moral conflicts can nonetheless ensue, and how best to address these challenges [45].…”
Section: Ways Of Addressing Resultant Moral Distressmentioning
confidence: 99%
“…This Federation recommends, too, that state boards use supportive or normalizing language about obtaining mental health treatment. But only one state has thus far adopted all these guidelines [51]. Physicians in states in which initial license applications fail to follow such guidelines are 29% more reluctant to seek mental health treatment [52].…”
Section: Ways Of Addressing Resultant Moral Distressmentioning
confidence: 99%
“…A 2021 review showed that 39 states now ask questions focusing only on current impairment rather than illness, diagnosis, or previous treatment and that 17 no longer require disclosure of mental health conditions. 7 According to the Dr Lorna Breen Heroes' Foundation, as of November 2022, 19 states have medical licensure applications that align with recommendations from the FSMB (https://drlornabreen.org/ removebarriers/ ). However, it is important to note that these data only focus on physicians, and not other members of the health care workforce.…”
Section: Change Is Happeningmentioning
confidence: 99%
“…19 The 'State' of disability inclusion can be measured by systemic barriers to access, which lead to disparate outcomes for trainees with disabilities compared to their non-disabled peers. 20 These barriers are present in several domains, including: admissions, 3,21,22 instruction, 18 process, 16 access to accommodation in medical training and licensure exams, 23,24 lack of knowledge regarding reasonable and appropriate accommodation/ adjustments 3,16 and discriminatory practices for physician licensure. 24,25 In the context of an ableist and historically hostile environment.…”
Section: Deming's Point 3: Cease Dependence On Inspection To Achieve ...mentioning
confidence: 99%
“…20 These barriers are present in several domains, including: admissions, 3,21,22 instruction, 18 process, 16 access to accommodation in medical training and licensure exams, 23,24 lack of knowledge regarding reasonable and appropriate accommodation/ adjustments 3,16 and discriminatory practices for physician licensure. 24,25 In the context of an ableist and historically hostile environment. 15 The need to self-identify a disability will also result in an underreporting of disability and a cadre of trainees who are silently suffering, never truly having full access to our programmes and never reaping the benefits of feeling included in the medical community.…”
Section: Deming's Point 3: Cease Dependence On Inspection To Achieve ...mentioning
confidence: 99%